Dimensions of politics in the works of Marlene Streeruwitz - Endreva, Maria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
Marlene Streeruwitz’s aesthetic concept sees literature as a political gesture that reveals the traditional power mechanisms for the oppression of certain social groups and leads to knowledge. The political nature of literature raises the question of the contours of politics in Streeruwitz’s works. In the article, various aspects of this term are listed based on her essayistic work, so that the concept of the political nature of literature is illustrated. This happens in three stages. After Streeruwitz’s contextualization of politics, the second step is to list her most important aesthetic views, because it is precisely aesthetics that build a bridge to the political. In the third part of the paper, three topoi of the political - literature, war and the body - are highlighted.
Keywords: Marlene Streeruwitz; politics; resistance; literary aesthetics; feminism